The Relationship Between Social Support and Work Stress on Married Female Police in Sidoarjo Regency: Hubungan Antara Dukungan Sosial dengan Stres Kerja pada Polisi Wanita yang Sudah Menikah di Kabupaten Sidoarjo - Prasinta, Cindy; Widyastuti, Widyastuti (Indonesian Journal of Education Methods Development, 2022)
This research was conducted because there is still a phenomenon of female police officers who have high work stress. This study aims to determine the relationship between social support and work stress on married female police officers at the Sidoarjo Police Station. The research method is correlational quantitative. The population used is female police who serve in the jurisdiction of the Sidoarjo Police, who are active, totaling 117 members and the sample used is 98 married female police officers. The data collection technique used is the reliability social support scale = 0.947 and the reliability work stress scale = 0.931. The results of the analysis obtained that the correlation coefficient (rxy) -0.428 with a significance value of 0.000 <0.05 this research hypothesis is accepted. That is, there is a significant negative relationship between social support and work stress on married female police officers at the Sidoarjo Police Station. Social support provides an effective contribution of 17.5% to the work stress variable and 82.5% is influenced by other variables. Keywords – Social Support, Job Stress, Policewomen